Seeds Characteristics of Gelam (Meulaleca leucadendra): Seed Maturity, Morphology, Germination and Storability - Dede J. Sudrajat (Jurnal Perbenihan Tanaman Hutan, 2016)
Gelam (Meulaleuca leucadendra (L.) L.) is a potential species for construction timbers adapted to degraded swamp forest. Cultivation of this species is still limited and needs supporting of information of seed procurement technology, such as seed maturity, germination technique and storability. The present paper deals with assessing of seed maturity, morphology, germination and storability of the species. The seeds were collected from three natural populations, i.e. Landasan Ulin, Gasing, and Jabiren, and tested in a laboratory. The results showed that seed maturity can be identified from source of fruit/stalk. Seeds from the second and third fruit stalks resulted the best germination capacity,i.e 984 seedlings-0.1 g  and 809 seedlings -0.1  g , repectively. Fruit morphology, seed germination, and storability were significantly different among populations. Fruit from Gasing with length of 3.81 mm, diameter  of 3.79 mm and weight of 0.037 g  had higher sizes than fruits from Landasan Ulin and Jabiren. The best seed germination of the three seedlots was resulted from top paper method with 12 hours lighting period.   In the nursery practices, the mixed media of sand and rice husk charcoal (1:1 v/v) gave the best result of germination. The best storage of seeds was refrigerator room wraped by impermeable plastic bag. Seeds from Jabiren provided the best germination and storability that gave   a germination capacity of 925seedlings-0.1g and 731 seedlings-0.1 g before and after storage for one year, respectively.